2017
DOI: 10.1101/115188
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Learning to See Again: Biological Constraints on Cortical Plasticity and the Implications for Sight Restoration Technologies

Abstract: The "bionic eye" -so long a dream of the future -is finally becoming a reality with retinal prostheses available to patients in both the US and Europe. However, clinical experience with these implants has made it apparent that the vision provided by these devices differs substantially from normal sight.Consequently, the ability to learn to make use of this abnormal retinal input plays a critical role in whether or not some functional vision is successfully regained. The goal of the present review is to summari… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 219 publications
(289 reference statements)
0
23
0
1
Order By: Relevance
“…The shader then used these values to generate each phosphene's tail, following the underlying axon fibres. The tail's brightness would dissipate as a function of the distance from its phosphene, using the activation function described in [25]. Finally, the tails were superimposed on top of the original phosphene image.…”
Section: Simulation Of Prosthetic Visionmentioning
confidence: 99%
“…The shader then used these values to generate each phosphene's tail, following the underlying axon fibres. The tail's brightness would dissipate as a function of the distance from its phosphene, using the activation function described in [25]. Finally, the tails were superimposed on top of the original phosphene image.…”
Section: Simulation Of Prosthetic Visionmentioning
confidence: 99%
“…The model has been shown to generalize across individual electrodes, patients, and devices, as well as across different experiments. Detailed methods of how the model was validated can be found in [HGW + 09], [NFH + 12], [BRBF17]. Here we provide a brief overview of the model cascade.…”
Section: Computational Model Of Bionic Visionmentioning
confidence: 99%
“…One major challenge in the development of retinal prostheses is predicting what patients will see when they use their devices. Interactions between implant electronics and the underlying neurophysiology cause nontrivial perceptual distortions in both space and time [FB15], [BRBF17] that severely limit the quality of the generated visual experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies under simulated prosthetic vision identified a visual angle of 30 degrees as the minimal requirement to efficiently complete everyday mobility and manipulation tasks [27][28][29][30] . However, this number might underestimate the real needs of retinal prostheses' users, which exhibit poor performance in those tasks, due to the perceptual learning and behavioural adaptation issues to the new form of partial and spatially fractioned artificial vision 31,32 . The visual angle is a significant bottleneck preventing patients from achieving an efficient performance and a sustainable experience.…”
mentioning
confidence: 99%